2023
DOI: 10.21037/jtd-22-1414
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year survival following lung transplantation

Abstract: Background Lung transplantation median survival has seen improvements due to recognition of short-term survival factors but continues to trail behind other solid organs due to limited understanding of long-term survivorship. Given the creation of the United Network for Organ Sharing (UNOS) database in 1986, it was difficult to accrue data on long-term survivors until recently. This study characterizes factors impacting lung transplant survival beyond 20 years, conditional to 1-year survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, donor smoking history has been associated with decreased recipient survival ( 20 ). This study has identified donor cigarette use as a moderate long-term risk factor independent of its short-term effect ( 13 ), suggesting that carbon black from smoking may have a hand in the CLAD.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, donor smoking history has been associated with decreased recipient survival ( 20 ). This study has identified donor cigarette use as a moderate long-term risk factor independent of its short-term effect ( 13 ), suggesting that carbon black from smoking may have a hand in the CLAD.…”
mentioning
confidence: 96%
“…The current study by Miggins et al is the first to explore these factors in transplant recipients who have survived multiple decades ( 13 ). Their results have redemonstrated what we know thus far regarding single versus bilateral lung transplants.…”
mentioning
confidence: 98%